Cash Movement: The Heart of Income Measurement. - Carson, A. B. (The Accounting Review, 1965)
Abstract This article presents information on cash movement, which should be the foundation of periodic income measurement. It is contended that most people think that periodic business net income or loss is closely linked to certain of the movements of cash into and out of the business, and that, while a simple periodic matching of cash receipts and disbursements rarely gives a meaningful measure of net income, cash movement can be objectively measured and is a far better starting point for income determination than value, a highly subjective matter. It is further contended that even if the proposals to link value changes closely to income measurement were sound in principle and feasible, the likelihood of their gaining widespread understanding and acceptance is negligible. If these contentions are valid, it is incumbent upon accountants to stray no further than absolutely necessary from cash movement in calculating periodic business income. It is noted that problems rarely exist in cases where there is a very close correlation between cash movement and revenue and expense realization or recognition.